THE IMPACT OF VIRAL MARKETING IN THE TOURISM INDUSTRY IN MALAYSIA POST COVID-19 PANDEMIC - Rakesh, Sarpal; Yeoh, Chiao Ying (INTI International University, 2022)
Viral marketing played a major role in tourism marketing for the government and private sector. This marketing strategies often referred to as electronic word-of-mouth (eWOM). Extensive research studies have been carried out on the mechanism and importance of viral marketing. However, there is a research gap on the viral marketing impact on the tourist destination in the COVID-19 pandemic crisis. The purpose of this paper is to discuss the impact of viral marketing or electronic WOM (eWOM) on a tourism destination choice after COVID-19, using the theory of planned behaviour (TPB). The intended outcome and purpose of the study is look at possible adaptive marketing strategies and approaches in the endemic stage of COVID-19. The effectiveness of viral marketing in promoting tourist destinations in Malaysia is studied in this literature view to identify the influence of viral content in tourist decision-making.